Active Learning Strategies in Synchronous Online Learning for Elementary School Students - Hatta, Puspanda; Aristyagama, Yusfia Hafid; Yuana, Rosihan Ari; Yulisetiani, Septi (Universitas Sebelas Maret, 2020)
The Covid-19 pandemic gives an impact on education field. The face-to-face learning pattern in schools has shifted to distance learning which is carried out online. The implementation of online learning during the pandemic forces a digital transformation in education, causing several problems, two of which are technology and human resources. This article discusses the appropriate online learning strategies to use during a pandemic, especially for synchronous interaction models. Qualitative research with a narrative approach was used to explore teachers' experiences in learning, especially those related to the form of interaction between teachers and students during the Covid-19 pandemic. Active learning was chosen based on the results of observations and literature review through journal articles and proceedings that discuss interactive distance learning methods. Active learning strategies assisted by video conferencing applications that can be applied in online learning in elementary schools include: the use of Student Response Systems; Think Pair Share; One Minute Paper; Small Group Discussion; and Short Student Presentations.